The Use of ‘Tuning In’ Strategy To Stimulate the Autonomous Learning in Listening Skill - Ahmad Junaedi; Amrang (Sekolah Tinggi Agama Islam Negeri Majene, 2022)
This study aimed to examine the students’ achievement in listening through the use of ‘Tuning In’ strategy by employing pre-experimental research method. The data collection instruments were listening test and questionnaire. The listening tests were given in the form of pre and post test to reveal whether or not ‘Tuning in’ strategy can improve the students’ achievement in listening. The questionnaire was given to identify the students’ autonomy in learning listening skill. There were 30 students randomly selected to participate in this study. The results revealed that the students’ listening ability taught by using ‘Tuning in’ strategy was increased. It is proved by the mean score of students’ post-test score 84.45 (good) while the mean score of the pre-test was 67.3 (fair). In addition, questionnaire indicates that the use of ‘Tuning in’ strategy can stimulate the students’ autonomous learning in listening.